Pengaruh Penambahan Aditif 2-EHN dan Asam Oleat pada Biosolar terhadap Konsumsi Bahan Bakar - Muhadi, Imam; Zainuri, Ach Muhib (Lembaga Yasin AlSys, 2024)
Biodiesel B30 is a blend of 70% conventional diesel fuel and 30% biodiesel, increasingly used as an environmentally friendly alternative. However, to enhance fuel performance and efficiency, the addition of additives such as 2-EHN (2-Ethylhexyl Nitrate) and oleic acid needs further study. This research aims to eval_uate the impact of these additives on diesel engine fuel consumption. The study uses an experimental method to explore the cause-and-effect relationship between independent and dependent variables with a quantitative approach. Collected data is analyzed using statistical techniques to measure and eval_uate the significance and strength of relationships between variables. Through experimental methods and statistical analysis, this research aims to provide a deeper and more scientific understanding of the phenomena being studied. The graph shows that fuel consumption increases with RPM. Oleic acid increases fuel consumption at both low and high RPMs. In contrast, 2-EHN reduces fuel consumption, especially at high RPMs. Overall, 2-EHN is more efficient than oleic acid in improving the performance of B30 biodiesel. The addition of 2-EHN to biosolar fuel reduces fuel consumption, particularly at high RPMs. B30 blends with 0.5% and 1% 2-EHN show better efficiency compared to blends without additives or with oleic acid. Conversely, adding oleic acid increases fuel consumption, especially at high RPMs, indicating lower efficiency.